A Prion Protein Gene Polymorphism at Codon 138 Modulates Chronic Wasting Disease Pathogenesis ... - Arifin, Maria Immaculata (Veterinary Medicine, 2021)
Prion diseases are fatal and infectious neurodegenerative diseases caused by prions. Chronic wasting disease (CWD) is a prion disease of cervids found in North America (NA), Scandinavia and South Korea. Although there are no reports of CWD in caribou (Rangifer tarandus spp.) in NA so far, previous findings show that reindeer (R. t. tarandus) are susceptible to CWD. Single amino acid substitutions (SAAS) within the cervid prion protein (PrP) sequence have been shown to prolong survival times and produce incomplete attack rates upon CWD infection. Prion protein SAAS have been found in caribou populations in NA, including a serine to asparagine substitution at codon 138 (S138N). Previous studies reported that animals harboring the N variant at this codon were either resistant or less susceptible to natural CWD prion exposure. Based on these reports, we hypothesized that the S138N PrP amino acid substitution modulates CWD pathogenesis. We report that the 138N allele frequency is rare among caribou in areas with ...